Detection of trends in extreme rainfall in the province of Ontario - Bougadis, John (University of Ottawa (Canada), 2003)
Information on intensity-duration-frequency (IDF) of rainfall is commonly required for the design, construction, and management of many water resources projects involving natural hazards, due to extreme rainfall events. Design storms (DS) are determined from IDF relationships. Many hydraulic structures (dams, weirs, culverts, storm sewer systems, etc.) are designed to serve 50 years or more into the future. Yet, these structures are being sized for the climatic conditions based on the past records, before climate change. Thus, new design methods accounting for climatic change are needed to prevent potential losses and damages resulting from under-design. This research addresses the issue of the effect of climate change on design storms. The major objectives of this study are to detect trends in extreme rainfall, and to estimate anticipated changes in return periods of extreme rainfall events due to trends. In this study, trends (which might be attributed to climate change) are estimated for different durations of annual extreme rainfall using the regional average Mann-Kendall's S trend test. Numerical analysis was performed on 44 rainfall stations from the province of Ontario, Canada for a 20 and 25 year time frame. (Abstract shortened by UMI.)
Keywords: Physical Geography.; Engineering, Civil.